Measurement of χc1(3872) production in proton-proton collisions at √s = 8 and 13 TeV - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2022)
The production cross-section of the χc1(3872) state relative to the ψ(2S) meson is measured using proton-proton collision data collected with the LHCb experiment at centre-of-mass energies of $$ \sqrt{s} $$= 8 and 13 TeV, corresponding to integrated luminosities of 2.0 and 5.4 fb−1, respectively. The two mesons are reconstructed in the J/ψπ+π− final state. The ratios of the prompt and nonprompt χc1(3872) to ψ(2S) production cross-sections are measured as a function of transverse momentum, pT, and rapidity, y, of the χc1(3872) and ψ(2S) states, in the kinematic range 4 < pT < 20 GeV/c and 2.0 < y < 4.5. The prompt ratio is found to increase with pT, independently of y. For the prompt component, the double ratio of the χc1(3872) and ψ(2S) production cross-sections between 13 and 8 TeV is observed to be consistent with unity, independent of pT and centre-of-mass energy.
Im Text ist "χc1" tiefgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecná, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 07.10.2022